2022
DOI: 10.3389/feart.2022.864279
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Occurrence State of Methane Molecules in Postmature Marine shales—A Case Analysis of the Lower Silurian Longmaxi Formation Shales of the Upper Yangtze Region in Southern China

Abstract: The Yangtze region in southern China is endowed with abundant marine shale gas. Methane molecules exist in either adsorption state or free state in postmature marine shales, depending on the components of shales. In this study, the core samples of the selected well in the Lower Silurian Longmaxi Fm. shales from the Sichuan Basin, upper Yangtze region, southern China, were taken as study objects. We carried out TOC content, organic matter maturity, mineral component, and core gas content analyses and isothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…A number of wells in the study area are selected to test the Leping formation physical characteristics by the nuclear magnetic resonance technology (NMR). The results showed that the Leping Formation carbonaceous shale gas reservoir in the study area has high porosity and relatively low permeability (Shan et al, 2015;Zhang et al, 2020c;Zhang et al, 2022a;Zhang et al, 2022b;Zhang et al, 2022c). The total porosity of mud shale ranges from 7.7 to 10.4% (Figure 8), and the permeability is generally less than 0.10 mD, with an average of about 0.005 mD.…”
Section: Physical Characteristicsmentioning
confidence: 84%
“…A number of wells in the study area are selected to test the Leping formation physical characteristics by the nuclear magnetic resonance technology (NMR). The results showed that the Leping Formation carbonaceous shale gas reservoir in the study area has high porosity and relatively low permeability (Shan et al, 2015;Zhang et al, 2020c;Zhang et al, 2022a;Zhang et al, 2022b;Zhang et al, 2022c). The total porosity of mud shale ranges from 7.7 to 10.4% (Figure 8), and the permeability is generally less than 0.10 mD, with an average of about 0.005 mD.…”
Section: Physical Characteristicsmentioning
confidence: 84%
“…Frontiers in Earth Science frontiersin.org technology of FIB-SEM which can help identify the mineral composition, the type of shale micro-nanometre pores can be effectively determined (Zhang et al, 2019c;Li et al, 2021c;Zhang et al, 2022d;Zhang et al, 2022e). In this study, FIB-SEM observation was carried out using an instrument of FEI HELIOS NANOLAB 650 SEM.…”
Section: Fib-sem Observationmentioning
confidence: 99%
“…This finding thus provides a direction for the exploration and development of oil and gas fields and the prediction of favorable reservoir zones in the Tazhong region within the Tarim basin. Urey, 1948, Kuypers et al, 1999, Li, 2022a, Li et al, 2019, Li et al, 2022b, Zhang et al, 2022a, Zhang et al, 2022b, Zhang et al, 2022c, Zhang et al, 2022d, Fan et al, 2022.…”
Section: Geological Significancementioning
confidence: 99%
“…These have generally undergone long periods of geological and environmentally driven changes, including repeated dissolution and filling caused by various factors and fluids. These reservoirs are characteristically very deeply buried, tectonically complex and highly heterogeneous (Li et al, 1996;Zhu et al, 2005), thus causing immense difficulties in predicting the location and character of deeply buried carbonate paleokarst reservoirs (Li, 2022a;Li et al, 2019;Li et al, 2022;Li et al, 2022b;Zhang et al, 2022a;Zhang et al, 2022b;Zhang et al, 2022c;Zhang et al, 2022d).…”
Section: Introductionmentioning
confidence: 99%